Amide Proton Transfer‐Weighted Imaging Combined With Intravoxel Incoherent Motion for Evaluating Microsatellite Instability in Endometrial Cancer. Issue 2 (23rd June 2022) - Ma, Changjun; Tian, Shifeng; Song, Qingling; Chen, Lihua; Meng, Xing; Wang, Nan; Lin, Liangjie; Wang, Jiazheng; Liu, Ailian; Song, Qingwei
Abstract : Background: Microsatellite instability (MSI), caused by mismatch repair (MMR) protein defects that lead to uncorrectable mismatch bases, results in the accumulation of gene mutations and ultimately to tumors. Preoperative prediction of MSI can provide a basis for personalized and precise treatment of endometrial cancer (EC) patients. Purpose: To investigate amide proton transfer weighting (APTw) imaging combined with intravoxel incoherent motion (IVIM) in the assessment of MSI in EC. Study Type: Retrospective. Population: A total of 71 patients with EC (12 classified as the MSI group and 22 as the microsatellite stabilization [MSS] group after entering and leaving the group standard). Field Strength/Sequence: A 3.0 T/IVIM, diffusion‐weighted imaging (DWI) and APTw. Assessment: Amide proton transfer (APT) value, apparent diffusion coefficient (ADC), pure diffusion coefficient ( D ), pseudo diffusion coefficient ( D *), and perfusion fraction ( f ) were calculated and compared between MSI and MSS groups. Statistical Tests: The Kendall's W test; Mann–Whitney U‐test; Chi‐square test or Fisher's exact test; logistic regression analysis; Area under the receiver operating characteristic (ROC) curve (AUC); The Delong test; Pearson or Spearman correlation coefficients. The significance threshold was set at P  < 0.05. Results: APT and D * values of the MSI group were significantly higher than those of the MSS group. While ADC, D, and f values in the MSI group were significantly lower than those in the MSS group. The multivariate analysis revealed that only APT and D * values were independent predictors to evaluate the MSI status. And the ROC curves indicated that the combination of APT and D * values could distinguish the MSI status of EC with the highest diagnostic efficacy (AUC = 0.973), even without significant difference to those by APT (AUC = 0.894) or D * (AUC = 0.920) value separately ( P  = 0.149 and 0.078, respectively). Conclusion: Combination of APTw and IVIM imaging may serve as an effective noninvasive method for clinical assessment of MSI in EC. Evidence Level: 3 Technical Efficacy: Stage 2